INFESTASI CAPLAK IXODIDAE PADA SAPI LOKAL ACEH DI BALAI PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BPTU-HPT) INDRAPURI KABUPATEN ACEH BESAR - Leliana, Leliana; Rizalsyah, T (Jurnal Edukasi dan Sains Biologi, 2015)
The study was conducted from September 2015 to October 2015 with the aim to determining the prevalence and identification of Ixodidae ticks genera at Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Indrapuri in Aceh Besar district. A total of 550 adult ticks collected from half-body region of 238 infested cattle population. Four genera of hard ticks were identified. Accordingly, Boophilus (66.73%) was the most abundant tick followed by Rhipicephalus (22.90 %); while Ambylomma (7.64 %) and Hyalomma (2.73 %) were found to be the least prevalent tick generas at the study site. Overall prevalence of hard tick infestations on local cattle Aceh was 47.6%.The study indicated that there was high burden of ticks in the area. Thus, strategic tick control, application of acaricides aimed at reduction of ticks population and improvement of practical management for animal health officers on the problem of ticks are highly recommended.Â Key words: Ambylomma, cattle, Hyalomma, Rhipicephalus, tick species